Sosialisasi Upaya Pencegahan Covid 19 di Area Mesjid Taqwa Desa Huta Koje Kecamatan Angkola Barat Kabupaten Tapanuli Selatan - Siregar, Hotma Royani; Ritonga, Sukhri Herianto (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Covid-19 is a disease caused by a new type of corona virus that first appeared at the end of 2019 in Wuhan, China, which is currently causing a pandemic in almost the entire world. In an effort to prevent the spread of Covid-19 from spreading. The government urges all levels of society to take various preventive measures such as physical distancing, wearing masks, regularly washing hands, increasing body resistance and maintaining health. This socialization activity for the prevention of Covid 19 in the mosque area aims to increase knowledge and change the behavior of the community, especially the Taqwa mosque worshipers and mosque caretaker so that they can continue to make efforts to prevent the transmission of covid 19 during worship that will be carried out at the mosque during the month of Ramadan. This activity is carried out using posters. The results of the evaluation during the activity process resulted in an increase in participants' knowledge regarding efforts to prevent COVID-19.